Diversity, equity, inclusion and belonging in EAS: A microcosm of non-traditional education - Aviva Vincent; Leanne Nieforth; Kelsey Dayle John; Jamie Schafroth (Human-Animal Interactions)
Abstract The current global mental health crisis highlights a need for a focus on culturally relevant and accessible mental health and education services. One such sector is incorporating horses into mental health and learning interventions. The HERD Institute, an organization within this sector, offers education for practitioners in both equine facilitated psychotherapy (EFP) and equine facilitated learning (EFL). The HERD Institute centers diversity, equity, inclusion, and belonging (DEIB) within the practice of EFL and EFP. The objective of this study was to explore mental health clinician-based experiences and education-based practitioner experiences related to DEIB and systems of oppression within the HERD Institute’s learning environment as it then relates to participants’ own clinical or educational practice. Using a participatory action research framework, conversational, semi-structured interviews were completed. Interview responses were analyzed using thematic analysis. Three themes emerged: (1) identity and self-reflection with horses, (2) awareness of scope of practice, and (3) being in relationship. These findings elucidate the importance of explicit education of DEIB, the complexity of self-reflection and the innate desire to be in relationship with others, horses and the environment. The HERD Institute serves as a microcosm for other types of educational spaces evidencing a need to be intentional with DEIB education and practice.